Clinical and prognostic significance of various anemia types in pulmonary arterial hypertension - Waligóra, Marcin; Mrowicka, Maria; Pietrus, Miłosz; Daniek, Justyna; Kurczyna, Patrycja; Karnaś, Michał; Chaba-Karnaś, Weronika; Jonas, Kamil; Kopeć, Grzegorz (Frontiers in Medicine, 2025)
IntroductionCurrent risk models for pulmonary arterial hypertension (PAH) omit anemia, although it may aggravate symptoms and haemodynamics. We assessed whether anemia and its subtypes add prognostic value.MethodsThis study included patients with idiopathic (IPAH) or connective tissue disease-associated PAH (CTD-PAH). Anemia was classified per WHO criteria into four subtypes: anemia of chronic disease (ACD), iron deficiency anemia (IDA), ACD/IDA overlap, and multifactorial anemia. Risk stratification followed the ESC 2022 guidelines and was reassessed after 12 months.ResultsAmong 127 patients (78.7% IPAH, 21.3% CTD-PAH) anemia was present in 22 patients (17.3%), including ACD (31.8%), ACD/IDA overlap (27.3%), and multifactorial anemia (40.9%). Patients with anemia had higher baseline risk strata, worse functional status, elevated NT-proBNP levels (p = 0.002), and shorter six-minute walk distances (p = 0.007). Anemia reduced the odds of clinical improvement by 75% (OR, 0.25; p = 0.02). Over a follow-up of 57.8 months, 64 patients (50%) died. ACD (HR, 2.43; 95% CI, 1.03–5.7; p = 0.04) and ACD/IDA (HR, 2.14; 95% CI, 1.04–4.41; p = 0.04) independently predicted mortality, even after adjustment for age and risk.ConclusionAnemia, particularly ACD and ACD/IDA, independently predicts a lower probability of achieving therapeutic goals within 12 months and is associated with higher long-term mortality, even after adjustment for the ESC/ERS 2022 recommended risk stratification.